(untitled) (Unilorin Journal of Lifelong Education, 2025)
The study investigated the influence of digital literacy skills on undergraduates’ use of WhatsApp in a Nigerian university. The study specifically sought to identify the digital literacy skills required to use WhatsApp by undergraduates; digital literacy skills possessed by undergraduates, purpose of WhatsApp usage and frequency of WhatsApp usage by undergraduates. The descriptive survey research design was adopted for the study, while University of Ilorin undergraduates were purposively chosen for the study. The stratified sampling technique was used to select 200 and 400 level students from six (6) departments in the university. The sample size for the study was 340 undergraduates. Questionnaire was used for data collection. Data analysis was done using descriptive statistics. The findings revealed that document creating and editing skills, web search skills, privacy skills, and internet usage skills were requisites for WhatsApp usage by undergraduates. The study identified computer literacy skills, web search skills, document creating and online editing skills, information retrieval skills and online/internet safety skills as the digital literacy skills possessed by the undergraduates. It was further revealed that most of the undergraduates use WhatsApp for academic related activities, project collaborations, social interaction, video/audio call meetings, and advertisement. Also, most of the undergraduates use WhatsApp on a regular basis for academic and non-academic purposes. It was recommended that universities should prioritise the development of digital literacy skills among undergraduates through workshops and coursework teaching on responsible use of digital tools such as the WhatsApp.